Prognostic value of miR-223 for pregnancy outcomes in patients with in vitro fertilisation and intracytoplasmic sperm injection - Qi Song; Jiajia Liu; Chen Li; Rongrong Liu; Nan Zhang; Hongzhi Shi (Journal of Obstetrics and Gynaecology, 2024)
Background This study aimed to analyse the expression of microRNA-223 (miR-223) in embryo culture medium and its correlation with pregnancy outcomes.Methods Two hundred and two patients undergoing in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) were divided into clinical pregnancy group (n = 101) and non-pregnant group (n = 101). The baseline data, clinical indicators, and the expression level of miR-223 in the embryo medium were compared between the two groups. Logistic regression analysis was used to analyse the relationship between each index and the pregnancy outcome. Receiver operator characteristic curve was carried out to evaluate the differential ability of miR-223 in pregnancy status. Bioinformatics methods were used to identify the target genes of miR-223 and elucidate their functions.Results Compared with pregnancy group, the non-pregnancy group exhibited a reduction in miR-223 expression (p < 0.001). Multivariate analysis revealed that miR-223 reduction was an independent factor for pregnancy failure (p < 0.05). The ROC curve demonstrated the discriminative capability of miR-223 in distinguishing pregnancy and non-pregnancy. In addition, bioinformatics analysis indicated that the target genes of miR-223 were predominantly located in the endocytic vesicle membrane and were primarily enriched in adenosine monophosphate-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signalling pathways.Conclusion In this study, levels of miR-223 in the embryo culture medium predicted pregnancy outcomes in subjects undergoing IVF/ICSI. Low expression of miR-223 was a risk factor for adverse pregnancy outcomes in subjects.